Using fuzzy multiple criteria decision making approaches for evaluating energy saving technologies and solutions in five star hotels: a new hierarchical framework - Mardani, A. (Elsevier Ltd, 2016)
The purpose of this study is to present a hierarchical framework for evaluating and ranking the important key energy-saving technologies and solutions in the 10 biggest Iranian hotels through integrating fuzzy set theory, as well as qualitative and quantitative approaches. The important key energy factors for the evaluation of energy saving technologies and solutions are gathered through a literature survey. This paper proposes a framework based on the fuzzy Delphi method, fuzzy multiple criteria decision-making, including fuzzy analytic hierarchy process and fuzzy techniques for order performance by similarity to ideal solution. In the fuzzy Delphi method step of the study, 17 key energy factors were selected from among a total of 40 energy factors and categorised into five groups. Fuzzy analytic hierarchy process was used for the ranking of 17 key energy factors, and fuzzy techniques for order performance by similarity to ideal solution employed for ranking of the 10 biggest Iranian hotels in different provinces. The results of this study revealed that the first rank of main groups was equipment efficiency (0.403), system efficiency (0.225) had the second rank, third rank was related to reduction of heating and cooling demands (0.151) and energy management (0.091) and renewable energy (0.083) had the fourth and fifth ranks respectively. In the ranking weights of 17 sub-groups of energy saving technologies and solutions, the results of fuzzy analytic hierarchy process showed that efficient solutions for active space cooling (0.662) was as first rank, building insulation had the second rank with score (0.541) and third rank was European Eco-label for tourist accommodation service (0.532).